A retrospective study comparing postoperative opioid prescribing practices in an academic medical centre. (September 2022) - Girard, Tanya; Dayan, Natalie; Wilson, Marnie Goodwin; Harris, Miriam; El-Messidi, Amira; Gosselin, Sophie; Fleiszer, David; Bonnici, André; Villeneuve, Eric; Lee, Todd C.; McDonald, Emily G.
Background: In the midst of the North American opioid crisis, identifying and intervening on drivers of high-risk opioid prescriptions is an important step towards reducing iatrogenic harm. Objectives: We aimed to identify factors associated with variations in high-risk opioid discharge prescriptions, following select surgical procedures, to guide future quality improvement initiatives. Methods: This retrospective cohort study analyzed 1322 patients who underwent select open pelvic and open abdominal surgeries between January 1 and December 31, 2017, in a tertiary health care centre in Montreal. Results: Patients who underwent open abdominal surgeries were prescribed significantly higher daily doses of morphine milligram equivalents (MME) (45 mg; interquartile range, 30-60), than patients who underwent either a caesarean delivery (20 mg, 20-20) or a hysterectomy (30 mg, 22-30). After adjustment for multiple potential confounders, abdominal surgery was associated with 4 times the odds of receiving more than 50 MME at hospital discharge compared with pelvic surgeries (odds ratio, 3.96; 95% confidence interval, 1.31-11.97). The availability of postoperative preprinted order sets with fixed high doses of opioids was also highly associated with the outcome. Conclusion: In our institution, some surgeries were more likely to receive high-risk opioid prescriptions at discharge. Efforts to optimize safer prescribing practices should address the creation and/or updating of preprinted order sets to reflect current best practice guidelines. This initiative could be overseen by hospital pharmacy and therapeutics committees.